Landscapes of the mind : worlds of sense and metaphor - Porteous, J. Douglas (John Douglas), 1943- (University of Toronto Press, 1990)
A landscape is a visual perception, the way in which we experience our environment through our eyes. In this provocative book Douglas Porteous ventures far beyond the visual into the myriad other sensory and existential perceptions -- otherscapes -- through which we encounter the worlds around and within us.